INFLUENCE OF PERCIEVED ORGANISATIONAL SUPPORT ON WORK LIFE BALANCE OF PUBLIC HEALTH CARE SECTOR EMPLOYEES - Mathew, Rincy V. (International Journal of Psychosocial Rehabilitation, 2020)
Beliefs of perceived organizational support to employees play a crucial role in the success and effectiveness of the employees. Individuals develop global beliefs concerning the extent to which the organizations value their contribution and careers about their well-being. The purpose of the present study is to test the nature of relationship between perceived organizational support and work life balance among health sector employees in South India. Even though all the three major dimensions of perceived organizational support are positively related to the worklife balance, in the present study the reduced level of work life balance in majority of the respondents reveals the lack of availability of perceived organizational support. The study recommends that perceived organizational support may be a distinctive factor in increasing the work life balance levels of employees to optimal levels in organizations.